2008
DOI: 10.1158/1535-7163.mct-08-0050
|View full text |Cite
|
Sign up to set email alerts
|

Human endothelial precursor cells express tumor endothelial marker 1/endosialin/CD248

Abstract: Angiogenesis occurs during normal physiologic processes as well as under pathologic conditions such as tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…The tubes/networks that MSC can establish may provide structural support in vivo as stroma or could potentially serve as a framework for vascular development during periods of active angiogenesis. Anti-endosialin was also effective at preventing tube/network formation by pericytes and endothelial precursor cells indicating that targeting endosialin can influence multiple cell types which contribute to tumor growth associated with vasculature and stroma (40,41).…”
Section: Discussionmentioning
confidence: 98%
“…The tubes/networks that MSC can establish may provide structural support in vivo as stroma or could potentially serve as a framework for vascular development during periods of active angiogenesis. Anti-endosialin was also effective at preventing tube/network formation by pericytes and endothelial precursor cells indicating that targeting endosialin can influence multiple cell types which contribute to tumor growth associated with vasculature and stroma (40,41).…”
Section: Discussionmentioning
confidence: 98%
“…To this end, we examined the expression of endothelial precursor marker CD133, 30 CD248 (endosialin), 31 along with early and late mural cell markers calponin, desmin, and smooth muscle-␣ actin. Expression of CD133 and CD248 indicates that LEC/KSHV express endothelial precursor cell markers ( Figure 2A-B).…”
Section: Endothelial and Mural Cell Precursor Characteristics In Ks Cmentioning
confidence: 99%
“…15 Subsequently, TEM-1/collagen IV co-localization was confirmed by confocal microscopy. 10 Other studies have demonstrated the importance of TEM-1 in regulating proliferation, 12 tube formation on matrigel, 11,16 and cell migration. 11,12 However, the exact mechanism(s)…”
Section: Introductionmentioning
confidence: 99%